Linear Algebra Examples
[987345210]⎡⎢⎣987345210⎤⎥⎦
Step 1
Set up the formula to find the characteristic equation p(λ).
p(λ)=determinant(A-λI3)
Step 2
The identity matrix or unit matrix of size 3 is the 3×3 square matrix with ones on the main diagonal and zeros elsewhere.
[100010001]
Step 3
Step 3.1
Substitute [987345210] for A.
p(λ)=determinant([987345210]-λI3)
Step 3.2
Substitute [100010001] for I3.
p(λ)=determinant([987345210]-λ[100010001])
p(λ)=determinant([987345210]-λ[100010001])
Step 4
Step 4.1
Simplify each term.
Step 4.1.1
Multiply -λ by each element of the matrix.
p(λ)=determinant([987345210]+[-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2
Simplify each element in the matrix.
Step 4.1.2.1
Multiply -1 by 1.
p(λ)=determinant([987345210]+[-λ-λ⋅0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.2
Multiply -λ⋅0.
Step 4.1.2.2.1
Multiply 0 by -1.
p(λ)=determinant([987345210]+[-λ0λ-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.2.2
Multiply 0 by λ.
p(λ)=determinant([987345210]+[-λ0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
p(λ)=determinant([987345210]+[-λ0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.3
Multiply -λ⋅0.
Step 4.1.2.3.1
Multiply 0 by -1.
p(λ)=determinant([987345210]+[-λ00λ-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.3.2
Multiply 0 by λ.
p(λ)=determinant([987345210]+[-λ00-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
p(λ)=determinant([987345210]+[-λ00-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.4
Multiply -λ⋅0.
Step 4.1.2.4.1
Multiply 0 by -1.
p(λ)=determinant([987345210]+[-λ000λ-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.4.2
Multiply 0 by λ.
p(λ)=determinant([987345210]+[-λ000-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
p(λ)=determinant([987345210]+[-λ000-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.5
Multiply -1 by 1.
p(λ)=determinant([987345210]+[-λ000-λ-λ⋅0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.6
Multiply -λ⋅0.
Step 4.1.2.6.1
Multiply 0 by -1.
p(λ)=determinant([987345210]+[-λ000-λ0λ-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.6.2
Multiply 0 by λ.
p(λ)=determinant([987345210]+[-λ000-λ0-λ⋅0-λ⋅0-λ⋅1])
p(λ)=determinant([987345210]+[-λ000-λ0-λ⋅0-λ⋅0-λ⋅1])
Step 4.1.2.7
Multiply -λ⋅0.
Step 4.1.2.7.1
Multiply 0 by -1.
p(λ)=determinant([987345210]+[-λ000-λ00λ-λ⋅0-λ⋅1])
Step 4.1.2.7.2
Multiply 0 by λ.
p(λ)=determinant([987345210]+[-λ000-λ00-λ⋅0-λ⋅1])
p(λ)=determinant([987345210]+[-λ000-λ00-λ⋅0-λ⋅1])
Step 4.1.2.8
Multiply -λ⋅0.
Step 4.1.2.8.1
Multiply 0 by -1.
p(λ)=determinant([987345210]+[-λ000-λ000λ-λ⋅1])
Step 4.1.2.8.2
Multiply 0 by λ.
p(λ)=determinant([987345210]+[-λ000-λ000-λ⋅1])
p(λ)=determinant([987345210]+[-λ000-λ000-λ⋅1])
Step 4.1.2.9
Multiply -1 by 1.
p(λ)=determinant([987345210]+[-λ000-λ000-λ])
p(λ)=determinant([987345210]+[-λ000-λ000-λ])
p(λ)=determinant([987345210]+[-λ000-λ000-λ])
Step 4.2
Add the corresponding elements.
p(λ)=determinant[9-λ8+07+03+04-λ5+02+01+00-λ]
Step 4.3
Simplify each element.
Step 4.3.1
Add 8 and 0.
p(λ)=determinant[9-λ87+03+04-λ5+02+01+00-λ]
Step 4.3.2
Add 7 and 0.
p(λ)=determinant[9-λ873+04-λ5+02+01+00-λ]
Step 4.3.3
Add 3 and 0.
p(λ)=determinant[9-λ8734-λ5+02+01+00-λ]
Step 4.3.4
Add 5 and 0.
p(λ)=determinant[9-λ8734-λ52+01+00-λ]
Step 4.3.5
Add 2 and 0.
p(λ)=determinant[9-λ8734-λ521+00-λ]
Step 4.3.6
Add 1 and 0.
p(λ)=determinant[9-λ8734-λ5210-λ]
Step 4.3.7
Subtract λ from 0.
p(λ)=determinant[9-λ8734-λ521-λ]
p(λ)=determinant[9-λ8734-λ521-λ]
p(λ)=determinant[9-λ8734-λ521-λ]
Step 5
Step 5.1
Choose the row or column with the most 0 elements. If there are no 0 elements choose any row or column. Multiply every element in row 1 by its cofactor and add.
Step 5.1.1
Consider the corresponding sign chart.
|+-+-+-+-+|
Step 5.1.2
The cofactor is the minor with the sign changed if the indices match a - position on the sign chart.
Step 5.1.3
The minor for a11 is the determinant with row 1 and column 1 deleted.
|4-λ51-λ|
Step 5.1.4
Multiply element a11 by its cofactor.
(9-λ)|4-λ51-λ|
Step 5.1.5
The minor for a12 is the determinant with row 1 and column 2 deleted.
|352-λ|
Step 5.1.6
Multiply element a12 by its cofactor.
-8|352-λ|
Step 5.1.7
The minor for a13 is the determinant with row 1 and column 3 deleted.
|34-λ21|
Step 5.1.8
Multiply element a13 by its cofactor.
7|34-λ21|
Step 5.1.9
Add the terms together.
p(λ)=(9-λ)|4-λ51-λ|-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)|4-λ51-λ|-8|352-λ|+7|34-λ21|
Step 5.2
Evaluate |4-λ51-λ|.
Step 5.2.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
p(λ)=(9-λ)((4-λ)(-λ)-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2
Simplify the determinant.
Step 5.2.2.1
Simplify each term.
Step 5.2.2.1.1
Apply the distributive property.
p(λ)=(9-λ)(4(-λ)-λ(-λ)-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.2
Multiply -1 by 4.
p(λ)=(9-λ)(-4λ-λ(-λ)-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.3
Rewrite using the commutative property of multiplication.
p(λ)=(9-λ)(-4λ-1⋅-1λ⋅λ-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4
Simplify each term.
Step 5.2.2.1.4.1
Multiply λ by λ by adding the exponents.
Step 5.2.2.1.4.1.1
Move λ.
p(λ)=(9-λ)(-4λ-1⋅-1(λ⋅λ)-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4.1.2
Multiply λ by λ.
p(λ)=(9-λ)(-4λ-1⋅-1λ2-1⋅5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(-4λ-1⋅-1λ2-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4.2
Multiply -1 by -1.
p(λ)=(9-λ)(-4λ+1λ2-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4.3
Multiply λ2 by 1.
p(λ)=(9-λ)(-4λ+λ2-1⋅5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(-4λ+λ2-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.5
Multiply -1 by 5.
p(λ)=(9-λ)(-4λ+λ2-5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(-4λ+λ2-5)-8|352-λ|+7|34-λ21|
Step 5.2.2.2
Reorder -4λ and λ2.
p(λ)=(9-λ)(λ2-4λ-5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8|352-λ|+7|34-λ21|
Step 5.3
Evaluate |352-λ|.
Step 5.3.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
p(λ)=(9-λ)(λ2-4λ-5)-8(3(-λ)-2⋅5)+7|34-λ21|
Step 5.3.2
Simplify each term.
Step 5.3.2.1
Multiply -1 by 3.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-2⋅5)+7|34-λ21|
Step 5.3.2.2
Multiply -2 by 5.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7|34-λ21|
Step 5.4
Evaluate |34-λ21|.
Step 5.4.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3⋅1-2(4-λ))
Step 5.4.2
Simplify the determinant.
Step 5.4.2.1
Simplify each term.
Step 5.4.2.1.1
Multiply 3 by 1.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-2(4-λ))
Step 5.4.2.1.2
Apply the distributive property.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-2⋅4-2(-λ))
Step 5.4.2.1.3
Multiply -2 by 4.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-8-2(-λ))
Step 5.4.2.1.4
Multiply -1 by -2.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-8+2λ)
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-8+2λ)
Step 5.4.2.2
Subtract 8 from 3.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(-5+2λ)
Step 5.4.2.3
Reorder -5 and 2λ.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(2λ-5)
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(2λ-5)
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(2λ-5)
Step 5.5
Simplify the determinant.
Step 5.5.1
Simplify each term.
Step 5.5.1.1
Expand (9-λ)(λ2-4λ-5) by multiplying each term in the first expression by each term in the second expression.
p(λ)=9λ2+9(-4λ)+9⋅-5-λ⋅λ2-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2
Simplify each term.
Step 5.5.1.2.1
Multiply -4 by 9.
p(λ)=9λ2-36λ+9⋅-5-λ⋅λ2-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.2
Multiply 9 by -5.
p(λ)=9λ2-36λ-45-λ⋅λ2-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3
Multiply λ by λ2 by adding the exponents.
Step 5.5.1.2.3.1
Move λ2.
p(λ)=9λ2-36λ-45-(λ2λ)-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3.2
Multiply λ2 by λ.
Step 5.5.1.2.3.2.1
Raise λ to the power of 1.
p(λ)=9λ2-36λ-45-(λ2λ1)-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3.2.2
Use the power rule aman=am+n to combine exponents.
p(λ)=9λ2-36λ-45-λ2+1-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ2+1-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3.3
Add 2 and 1.
p(λ)=9λ2-36λ-45-λ3-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ3-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.4
Rewrite using the commutative property of multiplication.
p(λ)=9λ2-36λ-45-λ3-1⋅-4λ⋅λ-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.5
Multiply λ by λ by adding the exponents.
Step 5.5.1.2.5.1
Move λ.
p(λ)=9λ2-36λ-45-λ3-1⋅-4(λ⋅λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.5.2
Multiply λ by λ.
p(λ)=9λ2-36λ-45-λ3-1⋅-4λ2-λ⋅-5-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ3-1⋅-4λ2-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.6
Multiply -1 by -4.
p(λ)=9λ2-36λ-45-λ3+4λ2-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.7
Multiply -5 by -1.
p(λ)=9λ2-36λ-45-λ3+4λ2+5λ-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ3+4λ2+5λ-8(-3λ-10)+7(2λ-5)
Step 5.5.1.3
Add 9λ2 and 4λ2.
p(λ)=13λ2-36λ-45-λ3+5λ-8(-3λ-10)+7(2λ-5)
Step 5.5.1.4
Add -36λ and 5λ.
p(λ)=13λ2-31λ-45-λ3-8(-3λ-10)+7(2λ-5)
Step 5.5.1.5
Apply the distributive property.
p(λ)=13λ2-31λ-45-λ3-8(-3λ)-8⋅-10+7(2λ-5)
Step 5.5.1.6
Multiply -3 by -8.
p(λ)=13λ2-31λ-45-λ3+24λ-8⋅-10+7(2λ-5)
Step 5.5.1.7
Multiply -8 by -10.
p(λ)=13λ2-31λ-45-λ3+24λ+80+7(2λ-5)
Step 5.5.1.8
Apply the distributive property.
p(λ)=13λ2-31λ-45-λ3+24λ+80+7(2λ)+7⋅-5
Step 5.5.1.9
Multiply 2 by 7.
p(λ)=13λ2-31λ-45-λ3+24λ+80+14λ+7⋅-5
Step 5.5.1.10
Multiply 7 by -5.
p(λ)=13λ2-31λ-45-λ3+24λ+80+14λ-35
p(λ)=13λ2-31λ-45-λ3+24λ+80+14λ-35
Step 5.5.2
Add -31λ and 24λ.
p(λ)=13λ2-7λ-45-λ3+80+14λ-35
Step 5.5.3
Add -7λ and 14λ.
p(λ)=13λ2+7λ-45-λ3+80-35
Step 5.5.4
Add -45 and 80.
p(λ)=13λ2+7λ-λ3+35-35
Step 5.5.5
Combine the opposite terms in 13λ2+7λ-λ3+35-35.
Step 5.5.5.1
Subtract 35 from 35.
p(λ)=13λ2+7λ-λ3+0
Step 5.5.5.2
Add 13λ2+7λ-λ3 and 0.
p(λ)=13λ2+7λ-λ3
p(λ)=13λ2+7λ-λ3
Step 5.5.6
Move 7λ.
p(λ)=13λ2-λ3+7λ
Step 5.5.7
Reorder 13λ2 and -λ3.
p(λ)=-λ3+13λ2+7λ
p(λ)=-λ3+13λ2+7λ
p(λ)=-λ3+13λ2+7λ